2016
DOI: 10.1113/jp272738
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of the impact of stimulation intensity on neuroplastic after‐effects induced by transcranial direct current stimulation

Abstract: Contemporary non-invasive neuromodulatory techniques, such as transcranial direct current stimulation (tDCS), have shown promising potential in both restituting impairments in cortical physiology in clinical settings, as well as modulating cognitive abilities in the healthy population. However, neuroplastic after-effects of tDCS are highly dependent on stimulation parameters, relatively short lasting, and not expectedly uniform between individuals. The present study systematically investigates the full range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
287
5
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 333 publications
(341 citation statements)
references
References 67 publications
(168 reference statements)
24
287
5
7
Order By: Relevance
“…We think this is the reason why four recent studies found different results when they assessed tDCS test-retest reliability using Grand Mean values. Particularly, two studies tested the intra-individual consistency of M1-atDCS for repeated sessions showing a fair to good degree of reliability (ICC = 0.565 [29]; ICC = 0.738 [35]) of tDCS effects; in other words individual effects were consistent on different days. However, fairly worse results of intra-individual reliability have been reported by other investigations indicating a lack of reproducibility (ICC = −0.500 [27]; ICC = 0.062 [33]) for repeated tDCS sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We think this is the reason why four recent studies found different results when they assessed tDCS test-retest reliability using Grand Mean values. Particularly, two studies tested the intra-individual consistency of M1-atDCS for repeated sessions showing a fair to good degree of reliability (ICC = 0.565 [29]; ICC = 0.738 [35]) of tDCS effects; in other words individual effects were consistent on different days. However, fairly worse results of intra-individual reliability have been reported by other investigations indicating a lack of reproducibility (ICC = −0.500 [27]; ICC = 0.062 [33]) for repeated tDCS sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, only few studies exploring tDCS effects based on MEP measures have employed a control condition (see for review [23]), and those who performed this control generally do not present individual data [5, 35, 5053]. To date, only two studies that reported reliability of tDCS effects across multiple sessions included a sham condition and presented as well individual responses [33, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current intensity may be critical for a-tDCS motor response and recent findings suggest that excitability after-effects do not linearly correlate with stimulation intensity, as lower intensities (0.5 and 1 mA) display equal or great effects in comparison to higher intensities (21). Future studies should explore the intensity-response relationship between a-tDCS and explosive strength performance.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Previous studies have shown that prolongation of stimulation duration can lead to a switch of directionality of effects [2], and a similar switch from long-term depression to potentiation-like plasticity has been demonstrated for higher stimulation intensity [3]. Moreover, dependent on baseline excitability, different stimulation intensities seem to have maximum efficacy [4]. Thus systematic exploration of safety and effects of extended tDCS protocols is critical for identification of maximally efficient stimulation approaches.…”
mentioning
confidence: 99%